Factors that affect development of affordable housing in Nairobi County - Machuki, Sophia N. Kamau (Strathmore University, 2020)
The challenge of affordable housing remains front and central not only in developing but also in established economies. It is however more pronounced in the former than the latter countries given the economic hardships faced by a relatively higher population. In Kenya, recent developments – such as the 2018 signing of a memorandum of understanding (MOU) between the United Nations Office for Projects Service and the Government of Kenya indicate that initiatives are in place to address the challenge in the near future. However, despite government efforts, there are still over 2.2 million households without affordable housing. The author appreciates that such mainstream factors as inaccessibility to bank financing, prohibitive cost of building materials and government taxation are well researched. However, the impact of factors such as access to alternative financing options, use of nascent building technologies and unconventional government interventions, remain unaddressed. The objectives of this research therefore were; to establish the impact of alternative financing methods on provision of affordable housing in Nairobi County, to determine the impact of modern building technologies on provision of affordable housing in Nairobi County and to assess the impact of government interventions on the provision of affordable housing in Nairobi County. The researcher sought to collect data from 87 registered property developers in Nairobi County using structured questionnaires and to apply the use of multiple linear regression to assess the relationship between the variables. Given the three considered factors, access to alternative financing had the highest impact on the provision of affordable housing with modern building technologies presenting as the second most influential factor. Contrary to the researcher’s expectations and extant literature, government interventions were deemed to be of trivial and unverified impact – at the 95% confidence level – on the provision of affordable housing in Nairobi County.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Affordable housing_Nairobi County; Established economies